Enhancing Audit Quality: How Fraud Detection Mediates Personality Traits and Time Pressure - Bambang Pamungkas; Moermahadi Soerja Djanegara; Dewi Sarifah Tullah; Nurul Hidayah; Hasan Junaidi (Jurnal Kajian Akuntansi, 2026)
Audit quality remains a critical concern in the public sector as recurring audit failures continue to raise questions about auditors’ ability to detect misstatements and fraud. This study examines how internal auditor characteristics and external working conditions influence audit outcomes by analyzing the role of fraud detection as a mediating variable between personality traits, time pressure, and audit quality. Using a quantitative approach, data were collected from 369 public sector auditors at the Audit Board of the Repubic of  Indonesia and analyzed using PLS-SEM. The results show that personality traits and time pressure both have a significant positive influence on fraud detection, and fraud detection itself significantly improves audit quality. Mediation analysis further confirms that fraud detection partially mediates the relationship between personality traits and audit quality, as well as the relationship between time pressure and audit quality. These findings reinforce Attribution Theory by demonstrating that auditors’ behaviors are shaped by the interaction between individual dispositions and situational pressures. Practically, the study highlights the importance of competency development, personality-aligned recruitment, and structured workload governance. Future research is recommended to incorporate audit-technology-related variables such as data analytics capability and digital auditing tools to better capture emerging dynamics in fraud-oriented audit performance.